Arsenic exposure is associated with pediatric pneumonia in rural Bangladesh: a case control study. Issue 1 (December 2015) - George, Christine; Brooks, W.; Graziano, Joseph; Nonyane, Bareng; Hossain, Lokman; Goswami, Doli; Zaman, Khalequzzaman; Yunus, Mohammad; Khan, Al; Jahan, Yasmin; Ahmed, Dilruba; Slavkovich, Vesna; et al.
Abstract Background Pneumonia is the leading cause of death for children under 5 years of age globally, making research on modifiable risk factors for childhood pneumonia important for reducing this disease burden. Millions of children globally are exposed to elevated levels of arsenic in drinking water. However, there is limited data on the association between arsenic exposure and respiratory infections, particularly among pediatric populations. Methods This case control study of 153 pneumonia cases and 296 controls 28 days to 59 months of age in rural Bangladesh is the first to assess whether arsenic exposure is a risk factor for pneumonia in a pediatric population. Cases had physician diagnosed World Health Organization defined severe or very severe pneumonia. Urine collected during hospitalization (hospital admission time point) and 30 days later (convalescent time point) from cases and a single specimen from community controls was tested for urinary arsenic by graphite furnace atomic absorption. Results The odds for pneumonia was nearly double for children with urinary arsenic concentrations higher than the first quartile (≥6 μg/L) at the hospital admission time point (Odd Ratio (OR):1.88 (95 % Confidence Interval (CI): 1.01, 3.53)), after adjustment for urinary creatinine, weight for height, breastfeeding, paternal education, age, and number of people in the household. This was consistent with findings at the convalescent time point where the adjusted OR for children with urinary arsenic concentrations greater than the first quartile (≥6 μg/L) was 2.32 (95 % CI: 1.33, 4.02). Conclusion We observed a nearly two times higher odds of pneumonia for children with creatinine adjusted urinary arsenic concentrations greater than the first quartile (≥6 μg/L) at the hospital admission time point. This novel finding suggests that low to moderate arsenic exposure may be a risk factor for pneumonia in children under 5 years of age.